Perencanaan Pengembangan Website Portofolio dengan Sistem Manaj Emen Konten (CMS) untuk Bisnis Fotografi Menggunakan Metode User Centered Design - Fadhlan Zaki Darmansah; Muhammad Yordi Septian; Alya Putri Salsabila; Wien Kuntari (STIKes Ibnu Sina Ajibarang, 2025)
The development of photography technology and the need for digital marketing have encouraged photographers to utilize online media as a promotional tool. This research aims to plan the development of a Content Management System (CMS)-based portfolio website for photography businesses using the User-Centered Design (UCD) approach. The UCD approach ensures that the website design meets the needs of users through iterative stages, including needs analysis, prototype design, and evaluation. The results show that the designed website is able to fulfill the main user needs, such as easy-to-update photo galleries, informative service pages, and responsive contact forms. WordPress CMS was chosen due to its ease of use and design flexibility. With the implementation of UCD, the user satisfaction score increased from 70% to 90%. However, improved security features are recommended to prevent unauthorized access to the photo gallery. This research contributes to the development of efficient digital media to improve the competitiveness of photography businesses in the digital era.